CHANGES IN THE CONSUMPTION BEHAVIOR OF NURUL JADID BOARDING SCHOOL STUDENTS IN DAILY PHYSICAL APPEARANCE (CASE STUDY OF NURUL JADID BOARDING SCHOOL FEMALE STUDENTS) - Arrow Varala; Rifqoh Maulidah (IJED: International Journal of Economy Development Research, 2023)
This study aims to examine and describe the factors causing the consumptive behavior of female students at Pondok Pesantren Nurul Jadid in shaping their daily physical appearance, as well as to understand and describe how these female students implement Islamic consumption concepts. This objective is important because, in essence, the pesantren teaches principles of simplicity and wise consumption management in accordance with Islamic teachings. However, there is a gap between the practice of Islamic consumption principles taught by the pesantren and the consumptive behavior of the female students, particularly in the consumption of products related to physical appearance such as clothing, accessories, and excessive makeup. The lack of knowledge among the students regarding Islamic consumption concepts creates a misalignment with the teachings of Islamic simplicity and the minimalist lifestyle that has been promoted. Through a qualitative approach with a case study of the female students at Pondok Pesantren Nurul Jadid, this research delves deeper into how the factors causing the consumptive behavior of these students shape their daily physical appearance and how the principles of Islamic consumption are applied by the students through the pesantren’s policies. Data were collected through in-depth interviews and observation to explore key factors such as cultural, social, personal, and psychological influences that affect their consumption behavior. The results of the study indicate that: 1) The daily physical appearance of the female students is strongly influenced by these factors, which in turn affects their consumption behavior. 2) Although some students have an understanding of the principles of Islamic consumption, the implementation of these principles in practice has not been fully maximized.